Bioinspired Adhesives: A Phenol‐Amine Superglue Inspired by Insect Sclerotization Process (Adv. Mater. 43/2020). Issue 43 (26th October 2020) - Wang, Younseon; Jeon, Eun Je; Lee, Jeehee; Hwang, Honggu; Cho, Seung‐Woo; Lee, Haeshin
Abstract : Polyphenol materials have rapidly emerged as bioadhesives. However, nearly all exhibit low adhesion strength compared to commercial glues. In article number 2002118, Seung‐Woo Cho, Haeshin Lee, and co‐workers show that phenolamine can exhibit adhesive strength >6 MPa, comparable to commercial epoxy glues. The advantage of the phenolamine bioglue is its 100% water basis. It effectively seals various substrates including ceramics, wood, fabrics, plastics, metals, and even wounded skin without any harmful effects. Therefore, these findings are promising in both industrial and biomedical applications.